Cardiac Rehabilitation for Aboriginal and Torres Strait Islander people in Western Australia. Issue 1 (December 2016) - Hamilton, Sandra; Mills, Belynda; McRae, Shelley; Thompson, Sandra
Abstract Background Cardiovascular disease (CVD) is a leading cause of morbidity and mortality in Australia. Australian Aboriginal and Torres Strait Islander (Indigenous) people have higher levels of CVD compared with non-Indigenous people. Cardiac Rehabilitation (CR) is an evidence-based intervention that can assist with reducing subsequent cardiovascular events and rehospitalisation. Unfortunately, attendance rates at traditional CR programs, both globally and in Australia, are estimated to be as low as 10-30 % and Indigenous people are known to be particularly under-represented. An in-depth assessment was undertaken to investigate the provision of CR and secondary preveniton services in Western Australia (WA) with a focus on rural, remote and Indigenous populations. This paper reports on the findings for Indigenous people. Methods Cardiac rehabilitation and Aboriginal Medical Services (n = 38) were identified for interview through the Heart FoundationDirectory of Western Australian Cardiac Rehabilitation and Secondary Prevention Services 2012. Semi-structured interviews with CR coordinators were conducted and included questions specific to Indigenous people. Results Interviews with coordinators from 34 CR services (10 rural, 12 remote, 12 metropolitan) were conducted. Identification of Indigenous status was reported by 65 % of coordinators; referral and attendance rates of Indigenous patients differed greatly across WA. Efforts to meet the cultural needs of Indigenous patients varied and included case management (32 %), specific educational materials (35 %), use of a buddy or mentoring system (27 %), and access to an Aboriginal Health Worker (71 %). Staff cultural awareness training was available for 97 % and CR guidelines were utilised by 77 % of services. Conclusion The under-representation of Indigenous Australians participating in CR, as reported in the literature and more specifically in this study, mandates a concerted effort to improve services to better meet the needs of Indigenous patients with CVD as part of closing the gap in life expectancy. Improving access to culturally appropriate CR and secondary prevention in WA must be an important component of this effort given the high rates of premature cardiovascular disease affecting Indigenous people. Our findings also highlight the importance of good systematic data collection across services. Health pathways that ensure continuity of care and alternative methods of CR delivery with dedicated resources are needed.